Geronimo Stilton. Operation shufongfong : and other adventures [videorecording (DVD)]. (Entertainment One Film USA LLC, 2013)
The animated series centers on the life and adventures of the famous Geronimo Stilton, head of a media empire, a peaceful mouse and klutz extraordinaire, and his fearless young nephew Benjamin Stilton. Adventure always comes knocking on their door, launching them paws-first into capers in New Mouse City or in exotic locales around the world.